Extraction of chondroitin sulfate and type II collagen from sturgeon (Acipenser gueldenstaedti) notochord and characterization of their hybrid fibrils. (January 2023) - Meng, Dawei; Li, Wen; Leng, Xiaoqian; Takagi, Yasuaki; Dai, Zhiyuan; Du, Hao; Wei, Qiwei
Abstract: Chondroitin sulfate (CS) and undenatured type II collagen (Col II) are the two major, biological macromolecules of cartilage-related tissues. In this study, a new extraction. process was developed to obtain CS and Col II simultaneously. By this process, CS. and undenatured Col II were extracted from sturgeon notochord with the yields of 5.34, ± 0.74% and 45.25 ± 5.25%, respectively. The SEC-RI-MALLS result showed that the, average molecular weight of notochord CS was 38.4 kDa. FTIR NMR, and SAX-HPLC, results indicated the notochord CS was mainly composed of CS-A. The new extraction, process had no effect on the triple helical structure of Col II. To analyze the interaction, between the two macromolecules, the effect of CS on Col II fibril formation was, examined using turbidity assay and SEM observation. CS accelerated the completion, of Col II self-assembly and inhibited the lateral aggregation of fibrils. The results of this, study suggested that the sturgeon notochord is a valuable source of CS and Col II. The. new extraction method not only improves the utilization rate of sturgeon notochord, but, also reduces the waste of aquatic resources. CS and Col II derived from sturgeon, notochord have the potential for use in biomedical materials Graphical Abstract: ga1 Highlights: Chondroitin sulfate (CS) and collagen (Col II) extraction method was developed. Yields of CS and Col II from sturgeon notochord were suitable for industrialization. Sturgeon notochord CS was mainly composed by CS-A with molecular weight of 38.4 kDa. The method had no effect on secondary structure and fibril-forming ability of Col II. CS bound on Col II fibrils and inhibited the lateral aggregation of fibrils.